2004
DOI: 10.1007/s00442-004-1588-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of δ13C of photosynthetic products and ecosystem respiratory CO2 and their responses to seasonal climate variability

Abstract: This study investigated the relationship between delta13C of ecosystem components, soluble plant carbohydrates and the isotopic signature of ecosystem respired CO2 (delta13CR) during seasonal changes in soil and atmospheric moisture in a beech (Fagus sylvatica L.) forest in the central Apennine mountains, Italy. Decrease in soil moisture and increase in air vapour pressure deficit during summer correlated with substantial increase in delta13C of leaf and phloem sap soluble sugars. Increases in delta13C of ecos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
145
4
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(172 citation statements)
references
References 38 publications
21
145
4
2
Order By: Relevance
“…We also observed that there is a consistent trend of more negative d 13 C values in leaves when compared to branches. Similar patterns have been observed in a range of other studies (Terwilliger et al 2001;Scartazza et al 2004;Brandes et al 2006;Peuke et al 2006). On one hand, this may be a result of a higher lipid content in the membrane-rich chloroplasts, as it has been reported that lipids are depleted in 13 C compared with organic matter, acids, sugars and respired CO 2 (Hobbie and Werner 2004).…”
supporting
confidence: 89%
“…We also observed that there is a consistent trend of more negative d 13 C values in leaves when compared to branches. Similar patterns have been observed in a range of other studies (Terwilliger et al 2001;Scartazza et al 2004;Brandes et al 2006;Peuke et al 2006). On one hand, this may be a result of a higher lipid content in the membrane-rich chloroplasts, as it has been reported that lipids are depleted in 13 C compared with organic matter, acids, sugars and respired CO 2 (Hobbie and Werner 2004).…”
supporting
confidence: 89%
“…Carbon pools with shorter turnover times and thus a better-defined origin such as leaf soluble sugars (Brugnoli and Farquhar, 1988), phloem allocated carbon (e.g. Gessler et al, 2004;Scartazza et al, 2004) or even dark-respired δ 13 CO 2 of recent photosynthates (Barbour et al, 2011b) are therefore better indicators for recent changes in WUE ia , as outlined below (Sect. 2.2).…”
Section: Interpretation Of Leaf 13 C B and 18 O B In Relation To Stormentioning
confidence: 99%
“…Within the last ten years it was, however, shown that the transport of newly assimilated carbon within the plant and from the plant to the rhizosphere can also be followed by natural abundance stable isotope techniques (e.g. Scartazza et al, 2004;Brandes et al, 2006;Wingate et al, 2010b …”
Section: And 18 O Isotopes To Trace Plant Integrated Processes Amentioning
confidence: 99%
“…Discs were dried at 60 • C during two days, weighted and specific leaf area (SLA, cm 2 g −1 ) was computed. During the same period, phloem sap was collected from each tree with the method described by Scartazza et al (2004) and modified by Gessler et al (2004). On July 19, from 11:00 a.m. to 5:00 p.m., a thin strip of bark (2 cm long and 1 cm wide) still attached to the trunk was removed and plunged into tubes filled with 1 mL pure water for 4 h. This mixture was membrane filtered (0.45 μm pore size, Millipore), put into tin capsules and oven-dried at 60 • C over one day.…”
Section: Plant Measurementsmentioning
confidence: 99%